SAMPLE NUCLEIC ACID MEASUREMENT TEST KIT, REAGENT, AND APPLICATION THEREOF - ZHANG, Taisong; ZHANG, Pan; WANG, Shanchen; CHEN, Feifei (2025)
Provided are a reagent, method, and test kit for measuring sample nucleic acid. A strong alkaline nucleic acid extraction solution (the pH value being 10.5 to 12.5) is used to extract the nucleic acid in the sample; add directly the extracted nucleic acid into a PCR reaction solution (the pH value being 8.0 to 9.0) for neutralization; at the same time, carry out nucleic acid amplification and measurement. The present invention can measure the nucleic acid in different types of samples such as blood, blood plasma, whole blood, genital tract secretion, sputum, or urine. In the present invention, the extracted sample nucleic acid is neutralized in a PCR reaction solution instead of being neutralized during nucleic acid extraction, thereby effectively enhancing the nucleic acid extraction efficiency and PCR amplification efficiency, and substantially improving the accuracy and sensitivity of the sample nucleic acid measurement.